2010
DOI: 10.1088/0004-6256/140/3/785
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Kuiper Belt Binaries by Gravitational Collapse

Abstract: A large fraction of ∼100 km class low-inclination objects in the classical Kuiper Belt (KB) are binaries with comparable masses and a wide separation of components. A favored model for their formation is that they were captured during the coagulation growth of bodies in the early KB. However, recent studies have suggested that large, 100 km objects can rapidly form in the protoplanetary disks when swarms of locally concentrated solids collapse under their own gravity. Here, we examine the possibility that KB b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
324
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(354 citation statements)
references
References 77 publications
25
324
2
Order By: Relevance
“…Various models have been proposed to explain the formation of binary and multiple systems, such as the L 3 mechanism by Goldreich et al (2002), the L 2 s mechanism by Goldreich et al (2002), the chaos-assisted capture by Astakhov et al (2005), the collisional model by Durda et al (2004), the hybrid model by Weidenschilling (2002), the gravitational collapse by Nesvorný et al (2010), and the rotational fission model by Ortiz et al (2012b). A complete review of some of these mechanisms can be found in Noll et al (2008).…”
Section: Formation Of Binary and Multiple Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various models have been proposed to explain the formation of binary and multiple systems, such as the L 3 mechanism by Goldreich et al (2002), the L 2 s mechanism by Goldreich et al (2002), the chaos-assisted capture by Astakhov et al (2005), the collisional model by Durda et al (2004), the hybrid model by Weidenschilling (2002), the gravitational collapse by Nesvorný et al (2010), and the rotational fission model by Ortiz et al (2012b). A complete review of some of these mechanisms can be found in Noll et al (2008).…”
Section: Formation Of Binary and Multiple Systemsmentioning
confidence: 99%
“…Sheppard et al (2012) previously discussed in detail all possible (or impossible) formation models for this system. They considered two plausible scenarii: the L 3 mechanism based on gravitational capture proposed by Goldreich et al (2002), and the gravitational collapse mechanism studied by Nesvorný et al (2010).…”
Section: Formation Of Binary and Multiple Systemsmentioning
confidence: 99%
“…An advantage with gravitational instability is that, if the internal angular momentum of a gravitationally unstable pebble cloud is large, it naturally forms a binary planetesimal with mass ratio of ∼1 (Nesvorný et al 2010). The components form from the same material, so they will also have the same chemical composition and colour, in agreement with what is observed for binary Kuiper belt objects (Benecchi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Kuiper belt as a whole has a wide colour distribution, so this suggests that the components in binary Kuiper belt objects formed together; a similar co-formation explanation is not possible in models of binary formation through three-body encounters (Goldreich et al 2002) in the hierarchical coagulation formation mechanism. Nesvorný et al (2010) modelled the particle cloud with an N-body method with perfect sticking. The goal of this paper is to use more realistic collision outcomes based on laboratory experiments to model the collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of these collisions determine the sizes of the planetesimals which emerge from the contracting clouds. Nesvorny et al (2010) investigated the outcome of collapsing pebble clouds and found that an initial mean rotation of the cloud (which could be inherited from the overall rotation of the disk) leads typically to the formation of a binary planetesimal surrounded by particles clumps which can be interpreted as a swarm of smaller planetesimals. This model agrees with the observation that the classical cold component of the Kuiper belt -the most pristine planetesimals in the Solar System which have undergone very little collisional and dynamical evolution -have a very high binary fraction.…”
Section: Key Research Findingsmentioning
confidence: 99%